Transformasi Sebuah Tradisi Intelektual: Asal Usul dan Perkembangan Pendidikan Islam - M. Taufik (Al-Jami'ah: Journal of Islamic Studies, 1999)
Historians noticed that Muslim intellectuals experienced "gold age". However, in the l8tb century, it felt into deep whole. There are three reasons proposed, by historians: First, there were no social order that support Islamic modernity. Second, Because the Muslims lost their spirit. Inherited from their ancestors, Third, Because of the isolation of religious knowledge from secular intellectualism. The current article tries to explore the third reason by describing the process of intellectual transformation throughout Islamic history. The author also discusses its impact in the development of Islamic intellectualism in Indonesian educational system.